A Comparative Analysis of Cultural Terms in Arabic-Javanese Religious Texts Through the Lens of al-Hikam Aphorisms Translation - Anis, Muhammad Yunus; Syed Abdullah, Syed Nurulakla bin (Universitas Islam Negeri Raden Intan Lampung, 2023)
Local wisdom stood as a cornerstone of Indonesia's cultural richness. Regrettably, this invaluable asset, particularly in the form of